Simulations of the propagation of high-intensity laser pulses in discharge-ablated capillary waveguides - Spence, D; Hooker, S (IEEE, 2000)
An overview is given on the results of numerical simulations of the propagation of high-intensity pules through discharge-ablated capillary waveguides. The numerical code solves the paraxial wave equation for a plasma undergoing optical field ionization, and so accounts for refractive defocusing due to further ionization by the propagating pulse.